2014
DOI: 10.1007/s00248-014-0490-6
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic Communities Supplied by Ancient Organic Carbon Predominate in Deep Fennoscandian Bedrock Fluids

Abstract: The deep subsurface hosts diverse life, but the mechanisms that sustain this diversity remain elusive. Here, we studied microbial communities involved in carbon cycling in deep, dark biosphere and identified anaerobic microbial energy production mechanisms from groundwater of Fennoscandian crystalline bedrock sampled from a deep drill hole in Outokumpu, Finland, by using molecular biological analyses. Carbon cycling pathways, such as carbon assimilation, methane production and methane consumption, were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 66 publications
13
78
0
Order By: Relevance
“…The dominant populations in both the modern marine and old saline water biofilm formers were putative carbon- and nitrogen-fixers (MMG_Bin_93 representing 11.73% of the reads and OSG_Bin_24 representing 2.15% of the reads). The importance of previously unknown microorganisms with a simple, fermentative growth strategy has recently been recognized at the Äspö HRL [22] as well as at another site [20]. These earlier findings are consistent with the metabolic features of several biofilm populations identified here (e.g., MMR_Bin_23 and OSR_Bin_0).…”
Section: Resultssupporting
confidence: 88%
“…The dominant populations in both the modern marine and old saline water biofilm formers were putative carbon- and nitrogen-fixers (MMG_Bin_93 representing 11.73% of the reads and OSG_Bin_24 representing 2.15% of the reads). The importance of previously unknown microorganisms with a simple, fermentative growth strategy has recently been recognized at the Äspö HRL [22] as well as at another site [20]. These earlier findings are consistent with the metabolic features of several biofilm populations identified here (e.g., MMR_Bin_23 and OSR_Bin_0).…”
Section: Resultssupporting
confidence: 88%
“…However, in the shallower fracture zone, 180 m depth, where the ratio of active cells was higher, only a small sub-population was responsive to the methane or methanol amendment. Earlier, Purkamo et al (2014) suggested that heterotrophic mechanisms such as fermenting could be community supporting strategies at certain depths of Outokumpu deep biosphere. When comparing the activated bacterial population, it was seen that at 180 m depth the Pseudomonas genus (Gammaproteobacteria) formed the majority of the activated community, whereas in the original community they were in minority.…”
Section: Discussionmentioning
confidence: 99%
“…The lithology, hydrogeochemistry and gas composition of the drillhole and fracture zones have been described previously (Ahonen et al, 2011; Kietäväinen et al, 2013; Purkamo et al, 2013; Nyyssönen et al, 2014). The fracture zones at 180 and 500 m depth are situated in a metasedimentary rock sequence, predominated by mica schist/biotite gneiss (Purkamo et al, 2014). The residence time for the fracture waters have been estimated to be between 20 and 50 Ma (Kietäväinen et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, the metabolic capabilities of deep terrestrial subsurface microbial communities include the pathways covering, e.g., methanogenesis [9][10][11], anaerobic methane oxidation [12], acetogenesis [4,13], sulfate reduction [14-16], oxidation of sulfur by denitrification [17], and reduction of iron [14].The Outokumpu deep scientific drill hole, located in Eastern Finland, hosts a unique environment piercing through crystalline Precambrian bedrock and its numerous saline fluid filled fracture zones. The composition of the microbial communities and the geochemical characteristics of the Outokumpu deep subsurface have been studied in detail [11,[18][19][20][21][22][23][24][25][26][27]. The metabolic strategies of the microbial communities at different depths in Outokumpu have been estimated through functional gene analysis and metagenomes [11,21].…”
mentioning
confidence: 99%